Optimization of Curing Process Significant Parameter and Level via Simulation on Curing of Printed Pattern on Synthetic Leather Substrate - Ismail, Nur Atirah Atasha; Khirotdin, Rd. Khairilhijra (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Synthetic leather is a durable material with a similar appearance and durability to real leather at a lower cost, most commonly used in the printing industry for many purposes, from clothing such as jackets and skirts to accessories like belts, wallets, handbags, and even shoes. Ultraviolet printing (UV) has shown great potential in synthetic leather printing with good speed and quality. However, some drawbacks were found, including graphical structure easily cracked, the UV ink is not fully cured, causing material remains sticky or wet and giving an unpleasant odour causing some health problems due to over exposure to UV light. Therefore, research is required to resolve such issues based on the direct printing technique using eco-solvent ink and existing curing technique used. In this study, a simulation was conducted via Minitab software to characterise and optimise the significant and level of curing parameters to cure the ink properly for printing process on synthetic leather substrate. This contribution evaluates the optimum level for both the significant and level of input parameters correspond to line width and pattern edge response values. Four parameters, were identified for curing process including curing temperature, curing time, ink layer thickness and light source intensity. The obtained results show only curing temperature and curing time are significant with 3-level design for curing the synthetic leather substrates at 50°C, 60°C, 70°C, and at VSD_2, VSD_3 and VSD_4 respectively.